Initial models in conditionals: evidence from priming - Espino, Orlando; Santamaría, Carlos (The Spanish Journal of Psychology, 2008)
We examined the comprehension of different types of conditionals. We measured the reading time of sentences primed by different types of conditionals (Experiments 1 and 2). We found that the participants read not-p and not-q faster when it was primed by the conditional form p if q and they were slower to read p and q when it was primed by the conditional form p only if q. This effect disappeared in the second experiment, where the order of the elements was reversed (q and p and not-q and not-p). These results suggest that the conditional form p if q elicits an initial representation “from p to q” with two possibilities, while the conditional form p only if q elicits a reverse representation with only one possibility. The third experiment showed that there were effects of the order only for the conditional if p then q, which confirms the reverse representation hypothesis. We discuss the implications of these results for different theories of conditional comprehension.